Kingella kingae Bacteremia: A Case Series - Wijnants, Lieselotte; Van Wambeke, Inge; Van Aerschot, Kaatje (Belgian Journal of Paediatrics, 2025)
Background Up to the early 1990s, when culture techniques and molecular detection methods were developing, Kingella kingae was considered a rare bacterium in the human body. Meanwhile, K. kingae is regarded as a prime etiology of skeletal system infections in children between 6-48 months. In this case report, we will discuss three distinct cases of K. kingae bacteremia in young children. Cases Despite their different presentations, the three cases were unified by the common finding of a respiratory tract infection along the course of their illness. The severity of the disease varied among the cases; going from a mild upper airway infection to a septic child, however, antibiotic therapy, whether administered intravenously or otherwise, was consistently selected in all three instances, yielding favorable outcomes. Conclusion Kingella kingae is well known to cause septic arthritis. Other types of presentation are less well known and probably under-reported, as we will demonstrate here. It is therefore important to recognize these clinical courses and respond promptly with appropriate treatment for the patient. After all, there is always a risk of secondary endocarditis and osteomyelitis. However, the bacteriological identification of K. kingae can be challenging. Proper interpretation of blood cultures or utilization of genetic testing is therefore critical..